2018
DOI: 10.15406/mseij.2018.02.00073
|View full text |Cite
|
Sign up to set email alerts
|

Using hydrogel-biochar composites for enhanced cadmium removal from aqueous media

Abstract: Cadmium (Cd) is a common heavy metal and is often released into aquatic environment during mining activities and metallurgical processes. At high concentrations, Cd is highly toxic to most organisms and can be accumulated in organisms before entering human body through food chains. Many technologies have been developed to remediate Cd contamination, among which biochar is one of the most sustainable and promising. However, high pricing of biochar today is plaguing its large-scale applications. Therefore, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…The reason for the synergistic effect was linked to each single biochar particle scattered in the composite creating an ionic attraction field for attracting and retaining metallic ions such as Cd 2+. This ionic attraction field significantly extended the potential of each biochar particle to entrap ions within the cross-linked composite structure against large concentration gradient of ions (Li and Chen, 2018). The formation of many ionic attraction fields around the scattered biochar particles made it possible to overcome the ionic osmotic stress, the main factor regulating the sorption and release of ions in hydrogel materials (Wang et al, 2014).…”
Section: Hydrogel-assisted Remediation Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason for the synergistic effect was linked to each single biochar particle scattered in the composite creating an ionic attraction field for attracting and retaining metallic ions such as Cd 2+. This ionic attraction field significantly extended the potential of each biochar particle to entrap ions within the cross-linked composite structure against large concentration gradient of ions (Li and Chen, 2018). The formation of many ionic attraction fields around the scattered biochar particles made it possible to overcome the ionic osmotic stress, the main factor regulating the sorption and release of ions in hydrogel materials (Wang et al, 2014).…”
Section: Hydrogel-assisted Remediation Studiesmentioning
confidence: 99%
“…The few adsorption studies conducted so far have shown promising results. For example, a biochar-hydrogel composite with 5% biochar was shown to significantly increase the swelling ratio of the hydrogel to 1506%, which is almost twice the size of the untreated hydrogel (818%), demonstrating great potential for the removal of Cd from soil (Li and Chen, 2018). Application of a biochar-digestate composite improved removal efficiency of Pb by nearly 100% when the composite dosage was applied at 1 g L −1 .…”
Section: Biochar: a Promising Panaceamentioning
confidence: 99%
See 1 more Smart Citation
“…It assumes that adsorption takes place on homogenous site and ceases as sites become unavailable. The adsorption is thus monolayer without established interaction between the adsorbate [7,11,12]. Langmuir model is expressed with Equation 4. qe = Qm bCe 1 + bCe 4…”
Section: Langmuir Isothermmentioning
confidence: 99%
“…Utilization of bamboo as a raw material for wastewater treatment has been increasing in recent years. Researchers have developed a variety of adsorbents derived from bamboo, including bamboo-activated carbon [9][10][11], bamboo biochar [12][13][14], and bamboo aerogel [15][16][17] among others.…”
Section: Introductionmentioning
confidence: 99%